Window of audio-visual simultaneity is unaffected by spatio-temporal visual clutter - Van der Burg, Erik (Nature Publishing Group, 2014)
In the present study we investigate the rules governing the perception of audiovisual synchrony within spatio-temporally cluttered visual environments. Participants viewed a ring of 19 discs modulating in luminance while hearing an amplitude modulating tone. Each disc modulated with a unique temporal phase (40 ms intervals), with only one synchronized to the tone. Participants searched for the synchronised disc whose spatial location varied randomly across trials. Square-wave modulation facilitated search: the synchronized disc was frequently chosen, with tight response distributions centred near zero-phase lag. In the sinusoidal condition responses were equally distributed over the 19 discs regardless of phase. To investigate whether subjective synchrony in the square-wave condition was limited by spatial or temporal factors we repeated the experiment with either reduced spatial density (9 discs) or temporal density (80 ms phase intervals). Reduced temporal density greatly facilitated synchrony perception but left the synchrony bandwidth unchanged, while no influence of spatial density was found. We conclude that audio-visual synchrony is not strongly constrained by the spatial or temporal density of the visual display, but by a temporal window within which audio-visual events are perceived as synchronous, with a full bandwidth of ~185 ms.